Taking the bad with the good: The nexus between tourism and environmental degradation in the lower middle-income Southeast Asian economies - Ahmad, F. (Elsevier Ltd, 2019)
The contribution of tourism to economic development is an open secret but it is a double-edged sword. The opportunity cost for this significant share is environmental degradation without required measures to protect the environment. Using the Fully Modified Ordinary Least Squared approach from 1995 to 2014, this study aims to explore the nexus between tourism and environmental pollution for three lower middle-income Southeast Asian economies: Indonesia, the Philippines and Vietnam. This paper uses carbon emissions as a proxy for environmental pollution against tourist arrivals with a few control variables for analysis. The Zivot-Andrews unit root test is applied to deal with structural breaks in data and the Gregory-Hansen test for robustness. The results confirm a negative impact of tourism on the environment for Indonesia and the Philippines; however, tourism improves the environmental quality of Vietnam. This implies that the relationship varies for different countries in the same region, depending on the country-specific characteristics and corresponding policies to protect the environment. The impact of governmental policies also differs for high and lower middle-income countries as one size cannot fit all. This study provides a comprehensive milieu of the impact of tourism on the environment. The identified dominant factors can guide Southeast Asian and other developing countriesâ governments at all levels in systematically formulating policies; by using these policies, carbon emissions from tourism can be reduced efficiently, resulting in sustainable development in the region. Â© 2019 Elsevier Ltd